Can the Internet be used to Reach Parents for Family-Based Childhood Obesity Interventions? - Hohman, Katherine H. (2011)
OBJECTIVE: Identify socioeconomic correlates of computer/Internet use among parents of overweight preschool-aged children. METHODS: Studied 470 baseline participants in a trial to prevent obesity in children 2–6.9 years with BMI ≥ 95th percentile or 85th–95th percentile with one overweight parent. Interviews with parents used Health Information National Trends Survey (HINTS) questions. RESULTS/CONCLUSIONS: Ninety-four percent had home computers and 93% reported Internet usage. In adjusted models, parents with ≤ college degree (OR 4.8 [95% CI 1.2, 18.3]) or with household income ≤ $50,000 (OR 7.6 [95% CI 2.2, 26.8]) had decreased likelihood of computer ownership. Of parents who reported going on-line, 63% used Internet to look for health/medical information for themselves and 42% for their children. Parents with ≤ a college degree or with BMI <25 kg/m(2) were less likely to use Internet. Results support using the Internet for early childhood obesity prevention with enhanced outreach efforts for low socioeconomic families.